Supporting the circular economy transition using the emergent role of the Internet of Things - Mardani, Abbas; Jose Chiappetta Jabbour, Charbel; Köppen, Mario (Technological and Economic Development of Economy, 2024)
Supporting the circular economy transition using the emergent role of the Internet of Things. Technological and Economic Development of Economy, 30(2), pp. 338-343.